KOMPARASI MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN DARING DAN LURING PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI TITIAN TERAS H. ABDURRAHMAN SAYOETI JAMBI - Shouqi Isyana Tristantio; Afdhal Afdhal (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to: 1) examine the differences between student learning motivation using an online system and an offline system, and 2) examine whether student learning motivation using an offline system is better than student learning motivation using an online system. This research uses quantitative research. using data in the form of numbers to analyze information about what you want to know. The purpose of quantitative research is to determine the relationship between variables in a population. Based on the results of data analysis in research and discussion of the comparison of student learning motivation between online learning and offline learning, the following conclusions can be drawn: 1) The average score of student learning motivation in online learning is 114.93 with a high category, while the average score for online learning is 114.93. the average score of students' learning motivation in offline learning is 122.62 with a high category. 2) The results of hypothesis testing obtained tcount 0.8187 < ttable 1.68, it can be concluded that H0 is rejected and H1 is accepted, which means that there is a significant difference between student learning motivation in offline learning and online learning in Geography subjects. 3) Based on this explanation, it can be concluded that offline learning can increase students' motivation in learning Geography compared to offline learning in Class X Social Studies SMA Negeri Titian Teras H. Abdurrahman Sayoeti Jambi.